Review: Potensi Aktivitas Antibakteri Daun dan Bunga Telang (Clitoria ternatea L.) Terhadap Bakteri Penyebab Jerawat - I Gusti Ayu Sinta Amara Yuda; Ketut Widyani Astuti (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Acne is a skin disease caused by chronic inflammation involving the sebaceous glands, the body's immune reaction, follicular hyperkeratinization, inflammation, and excess bacterial colonization. One plant that can be used as an antibacterial is the leaves and flowers of telang (Clitoria ternatea L.). The telang plant belongs to the Fabaceae or legume family which has been widely used for traditional medicine. The purpose of this review article is to observe information regarding the potential antibacterial activity of telang leaves and flowers in extract form against acne-causing bacteria and to determine the content of chemical compounds that are useful in the plant's antibacterial activity. The research method used is literature study obtained online via Google Scholar, Pubmed, and Elsevier which was published in the 2018-2023 period. The results of the review article report that telang leaves and flowers have secondary metabolite compounds such as flavonoids, alkaloids, terpenoids, saponins and tannins which contribute to antibacterial activity. This antibacterial activity can inhibit acne causing bacteria, namely Straphylococcus aureus, Staphylococcus epidermidis, and Propionibacterium acnes by denaturing the bacteria or increasing cell wall permeability. Based on several studies, telang leaves and flowers have antibacterial activity with the ability of secondary metabolites of alkaloids, flavonoids, terpenoids, tannins, and saponins